A dual‐band antenna design for MIMO LTE applications with reduced ground effects. Issue 1 (16th September 2015) - Sim, Chow‐Yen‐Desmond; Chen, Chih‐Chiang; Lee, Yuan‐Lung
ABSTRACT: A dual‐band planar long term evolution (LTE) antenna design is initially proposed. The size of this proposed antenna is 40 mm × 15 mm × 0.8 mm, and its structure is meticulously designed to achieve reduce ground effects, so that the ground plane size can be altered without affecting the antenna's performance. The 6‐dB impedance bandwidths of both lower and upper operating bands of proposed antenna are 13.1% (695–790 MHz) and 37.6% (2200–3120 MHz), respectively. Minimum radiation efficiencies of up to 56% are also exhibited within the three LTE bands (LTE 700/2300/2600 MHz). This proposed antenna is later used as a two‐antenna multiple input multiple output (MIMO) system for laptop computer application, and because of its reduced ground effects, good envelope correlation coefficient (ECC) of less than 0.14 and 0.0022 are measured across the lower and upper operating bands, respectively. © 2015 Wiley Periodicals, Inc. Int J RF and Microwave CAE 26:80–87, 2016.